TFIID-specific yeast TAF40 is essential for the majority of RNA polymerase II-mediated transcription in vivo - Komarnitsky, Philip B. (Cold Spring Harbor Laboratory Press, 1999)
Many questions remain concerning the role of TFIID TBP-associated factors (TAFs) in transcription, including whether TAFs are required at most or only a small subset of promoters. It was shown previously that three histone-like TAFs are broadly required for transcription, but interpretation of this observation is complicated because these proteins are components of both TFIID and the SAGA histone acetyltransferase complex. Here we show that mutations in the yeast TFIID-specific protein Taf40 lead to a general cessation of transcription, even in the presence of excess TBP, suggesting that the TFIID complex is required at most promoters in vivo.